Correlation between Alcohol Consumption Habits, Age, and Gender with Health Quality of Life among Middle and High School Students in Bolaang Mongondow Regency - Ocrico Isa, Roi; Victoria Rombot, Dina; Ellen Manampiring, Aaltje (Indonesian Health Journal, 2024)
Alcohol is a dangerous psychoactive substance, one of the factors contributing to many diseases and injuries. A quarter of the world's population, aged 15-19 years old, consumes alcohol. Adolescence's physical, cognitive, and psychological aspects proliferate, making it crucial to forming health foundations. Indonesian adolescents' health-related quality of life is still low (7%). Previous studies have indicated a correlation between alcohol consumption, age, gender, and quality of life. This study aims to analyze the correlation between alcohol consumption, age, and gender with the health-related quality of life of junior high and high school students. Utilizing an analytical observational research design with a cross-sectional approach. A total of 406 secondary school students in Bolaang Mongondow Regency participated as respondents. The study employed a questionnaire and statistical analysis using Spearman's correlation test and logistic regression. The correlation test found a negative relationship between alcohol consumption habits (r = -0.115; p = 0.020) and age (r = -0.159; p = 0.001) with the health-related quality of life however, a non-significant positive relationship was found for gender (r = 0.090; p = 0.069). The OR value was 1.664 (p = 0.020) in the age group of 15-17 years compared to the 10-14 years. There was a correlation between alcohol consumption habits and age with the health-related quality of life of junior high and high school students. At the same time, gender was not significant. Age is the most influential variable.